2023
DOI: 10.1186/s12913-023-09701-3
|View full text |Cite
|
Sign up to set email alerts
|

A management perspective on resilience in healthcare: a framework and avenues for future research

Abstract: Recent major health shocks, such as the 2014–16 Ebola, the Zika outbreak, and, last but not least, the COVID-19 pandemic, have strongly contributed to drawing attention to the issue of resilience in the healthcare domain. Nevertheless, the scientific literature appears fragmented, creating difficulties in developing incremental research in this relevant managerial field.To fill this gap, this systematic literature review aims to provide a clear state of the art of the literature dealing with resilience in heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 144 publications
0
4
0
Order By: Relevance
“…Saulnier et al ( 19 ) described a gap between theory and practice and pledged to a revision of this framework. Furthermore, other, newer resilience frameworks also focus on the health system level ( 33 35 ). Haldane et al ( 21 ) developed a resilience framework at the system level that largely meets the results of this study but was developed specifically for resilience in managing COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Saulnier et al ( 19 ) described a gap between theory and practice and pledged to a revision of this framework. Furthermore, other, newer resilience frameworks also focus on the health system level ( 33 35 ). Haldane et al ( 21 ) developed a resilience framework at the system level that largely meets the results of this study but was developed specifically for resilience in managing COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…However, distinctions in their methodological approaches are evident. Agostini et al offered a framework grounded in clinical outcomes and patient satisfaction indices [ 24 ]. In contrast, Förster et al [ 25 ] accentuated the pivotal role of clinical leadership, effective communication, and the innovative integration of technology in bolstering resilience.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent health crises, such as the Ebola outbreak, Zika virus, and the COVID-19 pandemic, have underscored the importance of resilience in healthcare. A group researchers conducted a systematic literature review to provide a comprehensive understanding of resilience in healthcare (Agostini et al, 2023). Their study identified key dimensions of resilience, such as the approach (reactive vs. proactive) and the type of crisis (acute shocks vs. chronic stressors).…”
Section: Potential Avenues For Future Researchmentioning
confidence: 99%
“…Their study identified key dimensions of resilience, such as the approach (reactive vs. proactive) and the type of crisis (acute shocks vs. chronic stressors). Their research offers a novel classification framework that can guide future studies in this domain, emphasizing the need for proactive strategies to anticipate health challenges and reactive measures to respond effectively (Agostini et al, 2023).…”
Section: Potential Avenues For Future Researchmentioning
confidence: 99%